Effectiveness of the use of synthetic analytical structural methods against the ability to begin writing skills in elementary school students - Zulela MS; Reza Rachmadtullah; Vina Iasha (Jurnal Prima Edukasia, 2021)
This study aims to determine the effectiveness of the Use of the Effect of Synthetic Analytical Structural Methods on the Beginning Writing Skills of Elementary School Students. This study uses a quantitative method with a type of quasi-experimental research. The results of this study found that there was significant use of the influence of synthetic analytical structural methods on the ability to write skills at the beginning of grade 2 elementary school students. This is because the Synthetic Analytical Structural Method is a story approach accompanied by an image that contains synthetic analytic elements. Synthetic Analytical Structural method implementation learning techniques are writing card skills, syllable cards, word cards, and sentence cards, while some students look for letters, syllables and words, the teacher and some students stick to words arranged into meaningful sentences.